2005
DOI: 10.1111/j.1742-4658.2005.05082.x
|View full text |Cite
|
Sign up to set email alerts
|

Stage‐specific expression of Caenorhabditis elegans ribonuclease H1 enzymes with different substrate specificities and bivalent cation requirements

Abstract: An enzyme that specifically degrades the RNA strand of RNA-DNA hybrids was first characterized from extracts of calf thymus tissue [1] and was named ribonuclease H (RNase H; EC 3.1.26.4) [2]. This protein has also been identified in viruses [3], bacteria [4,5], and archaea [6,7], indicating the essential nature of its roles in cellular metabolism. Prokaryotic RNase H enzymes are divided by sequence similarity into three groups: HI, HII, and HIII. On the other hand, there are two types of eukaryotic RNase H: RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Interestingly, human genome contains one RNase H1 with dsRHbd and at least three pseudogenes related to RNase H1 with dsRHbd [40]. Although we previously showed that four RNase H1-encoding genes in Caenorhabditis elegans exhibited gene-specific expression patterns during development; one gene encodes RNase H1 with dsRHbd and other three gene encode RNase H1 without dsRHbd [41], it was also found that most of the eukaryotic genomes contained single-copy genes encoding RNase H1 with dsRHbd but RNase H1 without dsRHbd had rarely been identified in the same genome (data not shown). Functional characteristic of RNase H1 with dsRHbd seems to depend on eukaryotic species because disruptions of RNase H1 with dsRHbd resulted in lethal phenotype of fly [42] and mice [13] but showed normal growth in yeast [43] and trypanosoma [44].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, human genome contains one RNase H1 with dsRHbd and at least three pseudogenes related to RNase H1 with dsRHbd [40]. Although we previously showed that four RNase H1-encoding genes in Caenorhabditis elegans exhibited gene-specific expression patterns during development; one gene encodes RNase H1 with dsRHbd and other three gene encode RNase H1 without dsRHbd [41], it was also found that most of the eukaryotic genomes contained single-copy genes encoding RNase H1 with dsRHbd but RNase H1 without dsRHbd had rarely been identified in the same genome (data not shown). Functional characteristic of RNase H1 with dsRHbd seems to depend on eukaryotic species because disruptions of RNase H1 with dsRHbd resulted in lethal phenotype of fly [42] and mice [13] but showed normal growth in yeast [43] and trypanosoma [44].…”
Section: Discussionmentioning
confidence: 99%
“…RNase H1.1 has two potential start codons, the first will initiate a protein with a MTS. Interestingly, the abundance of the mRNA encoding RNase H1.1 increases dramatically at the same stage of development when the amount of mtDNA increases fivefold over the level present initially in the embryo [28]. Perhaps RNase H1.1 plays a role in C. elegans mtDNA replication.…”
Section: Rnases H1mentioning
confidence: 99%
“…Most eukaryotic organisms, including S. cerevisiae, have single genes encoding RNase H1, whereas three related RNase H1 proteins are present in Caenorhabditis elegans (3,18). RNase H1.0, a homolog of mouse RNase H1, does not have a canonical N-terminal MTS (3,18), but another gene encoding a unique form of RNase H1 (RNase H1.1) has no HBD but does have an MTS (5,18). Interestingly, regardless of the presence or absence of the extra N-terminal sequences, an AUG codon is present immediately prior to the HBD.…”
mentioning
confidence: 99%